Ottoman Woman in the Central Balkans: Between Stereotypes and Reality (16th-18th Century) - Amedoski (Serbia), Dragana (Bulletin of the Institute of Ethnography SASA, 2018)
The aim of this paper is to present the woman in the Central Balkans during the Ottoman period, as well as her role and position in the social life. First of all, we have discussed the established stereotypes and then, on the basis of some new and yet unused, as well as the already exploited archival sources and literature, we have shown the real situation. The paper presents the rights women had under the Sharia and Ottoman Kanuns, and the extent to which those rights were actually observed in the everyday life. We have paid special attention to the following segments of the social life of women: possession of movable and immovable property, the economic role of women as stewards of her own and her children’s assets, women as endowers, women's right to work. Key words: Ottoman woman, Balkans, Ottoman Empire, marriage, divorce